Evaluación de la capacidad de remoción de colorante azoico del carbón activado obtenido a partir de pulpa de café (2024)
Coffee is a widely consumed product in Colombia and around the world, but its production process generates around 784,000 tons of coffee waste. Therefore, to address this problem, coffee husk is used to produce activated carbon from coffee pulp, which is composed of lignin, hemicellulose and cellulose. Likewise, activated carbon plays a key role in the elimination of heavy metals and the solution of contaminated effluents, especially in the textile industry.